A survey of Indonesian otolaryngologist behavior in medical service during the CoVid-19 pandemic - Indra Zachreini; Jenny Bashiruddin; Susyana Tamin; Harim Priyono; Ika Dewi Mayangsari; Respati Ranakusuma; Natasha Supartono; Fikri Mirza Putranto; Dewo Aksoro; Selfiyanti Bimantara; Yussy Afriana Dewi; Kote Noordhianta; Bintang Napitupulu; Sagung Rai Indrasari; Nyilo Purnami; Tengku Siti Hajar Haryuna; Juliandi Harahap; Eka Savitri; Tjandra Manukbua (Oto Rhino Laryngologica Indonesiana, 2021)
Background: World Health Organization (WHO) announced a newly discovered virus that first identified in Wuhan, China on December 2019, namely SARS-CoV-2 as the cause of corona virus disease (COVID-19) which had become global pandemic. Doctors as medical practitioners are categorized as vulnerable group to be infected by corona virus, and many otorhinolaryngologists had been infected and even died in performing medical services. Among the causative factors why otorhinolaryngologists could get infected by corona virus is their behavior. Purpose: To assess the behavioral level of otorhinolaryngologists in medical services during Covid-19 pandemic. Method: Descriptive study with a cross sectional design. Research samples were otorhinolaryngologists in Indonesia who met the inclusions criteria. The samples were selected by consecutive sampling method, and obtained 1299 subjects. Behavioral level was assessed from 3 aspects: knowledge, attitude, and practice, which comprised of 12 questions. Result: It was found that 461 respondents had a good behavioral level (35.5%), 677 respondents had moderate levels (52.1%) and 161 respondents had low level (12.4%). There was a statistically significant correlation between knowledge with behavioral level, attitude with behavioral level, and practice with behavioral level (p=0.001). Conclusion: The study of behavioral level of otorhinolaryngologists in medical service during Covid-19 pandemic obtained the highest number was moderate level 677 respondents (57.2%), and there was a statistically significant correlations between the variable of knowledge with behavioral level, the variable of attitude with behavioral level, and the variable of practice with behavioral level (p=0.001).ABSTRAK Latar belakang: Organisasi kesehatan dunia (WHO) mengumumkan virus baru yang pertama kali muncul di Wuhan China, pada Desember 2019, yaitu SARS-CoV-2 sebagai penyebab corona virus disease 19 (Covid 19) dan menyatakan sebagai pandemi. Dokter sebagai tenaga kesehatan merupakan kelompok yang rentan terinfeksi virus corona dan berdasarkan laporan, sudah banyak dokter Telinga Hidung Tenggorok - Bedah Kepala Leher (THT-KL) yang terinfeksi bahkan meninggal dunia dalam pelayanan medis. Salah satu faktor penyebab dokter THT-KL terinfeksi oleh virus corona adalah tingkat perilaku dokter THT-KL. Tujuan: Mengetahui tingkat perilaku dokter THT-KL dalam melakukan pelayanan medis saat pandemi Covid 19. Metode: Penelitian deskriptif dengan rancangan studi potong lintang. Sampel penelitian adalah dokter THT-KL di Indonesia yang memenuhi kriteria inklusi. Teknik pengambilan sampel secara berurutan, dan mendapatkan 1299 sampel. Tingkat perilaku dinilai dari 3 aspek yaitu dimulai dari pengetahuan, sikap dan tindakan yang terdiri dari 12 pertanyaan. Hasil: Didapatkan tingkat perilaku responden dokter THT-KL dalam pelayanan medis pada pandemi Covid 19, tingkat perilaku baik sebanyak 461 responden (35,4%), tingkat sedang 677 responden (52,1%), dan tingkat kurang 161 responden (12.4%). Terdapat hubungan yang signifikan antara pengetahuan dan tingkat perilaku, sikap dengan tingkat perilaku dan tindakan dengan sikap perilaku (p=0,001). Kesimpulan: Didapatkan tingkat perilaku dokter THT-KL dalam pelayanan medis pada pandemi covid 19, terbanyak adalah tingkat perilaku sedang sebanyak 677 responden (57,2%), dan terdapat hubungan yang bermakna antara variabel pengetahuan dengan tingkat perilaku, variabel sikap dengan tingkat perilaku dan variabel tindakan dengan tingkat perilaku dokter THT-KL dalam pelayanan medis pada pandemi Covid 19, dimana nilai p = 0,001. Kata kunci: perilaku, dokter THT-KL, pandemic, Covid-19